IMPROVING STUDENTS’ SPEAKING FLUENCY THROUGH THE USE OF DNS - Awiliya, Robiatul; Supardi, Iwan; Wijaya, Bambang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2014)
Abstract: The purpose of this research is to improve the students’ speaking fluency through the use ofDrafting Note for Speaking (DNS). The method used is a classroom action research which consisted of 3 cycles. The subjects of this research were tenth grade students of MAN 1 Pontianak which were consist of 33 students. The result of data analysis showed that using Drafting Note for Speaking (DNS) improved the students’ speaking fluency along the cycle. First cycle was 39 points which were categorized into poor qualifications, the figure improved by 50 points qualified into poor to average in the second cycle, and 81 points qualified into good to excellent in the third cycle. Keywords: Speaking Fluency,Improvement, Drafting Note for Speaking (DNS) Abstrak: Tujuan dari penelitian ini adalah untuk meningkatkan kelancaran siswa dalam berbicara melalui penggunaan Penyusunan Catatan untuk Berbicara (DNS). Metode yang digunakan adalah penelitian tindakan kelas yang terdiri dari 3 siklus. Subjek penelitian ini adalah siswa kelas X MAN 1 Pontianak yang terdiri dari 33 siswa. Hasil analisis data menunjukkan bahwa menggunakan Penyusunan Catatan untuk Berbicara (DNS) meningkatkan kelancaran berbicara siswa sepanjang siklus. Sikluspertamaadalah39poinyangdikategorikankedalamkualifikasiburuk, skorditingkatkanmenjadi50 poindengan kualifikasiburuk kerata-ratapadasikluskedua, dan81poin yangdikategorikandalam kualifikasibaikke yang sangatbaikpadasiklusketiga. Kata kunci: Kelancaran berbicara, Peningkatan, PenyusunanCatatanuntukBerbicara (DNS)